Priests performing the Abhishekam ritual - Mumbai Archive Project Team (Jio Institute, 2024)
Priests at the temple perform the abhishekam ritual, which involves the ceremonial bathing of the mukhalingam with sacred items, each poured while chanting specific mantras. These items include water, milk, yogurt, honey, clarified butter, coconut water, and sandalwood paste.